NAVIGATING THE LABYRINTH: A COMPREHENSIVE STUDY OF INTRICATE DYNAMIC STRATEGIES FOR ECONOMIC MANAGEMENT IN A COMPLEX GLOBALIZED ENVIRONMENT - Subhan Subhan; Surni; Dwi Koerniawati; Suharyono; Elman Johari (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
This comprehensive study delves into the intricate realm of dynamic economic strategies, offering a nuanced exploration of their application for effective economic management in the ever-evolving globalized environment. The modern economic landscape is marked by unprecedented transformations, necessitating a profound understanding of strategies that navigate this labyrinth of complexities. This research is anchored in unraveling the nuanced dynamics inherent in economic management, emphasizing the indispensable attributes of adaptability, resilience, and forward-thinking approaches. Employing an interdisciplinary lens, the study meticulously examines successful case studies, evaluates ongoing changes within the global economy, and proposes refined strategies tailored for policymakers and stakeholders. The research seeks to contribute valuable perspectives to the discourse on navigating economic complexities in an interconnected world by synthesizing insights from diverse disciplines, including economics, technology, and policy studies. This study aims to provide a comprehensive framework beyond conventional analyses, offering actionable insights for those steering economic policies in an era of rapid transformations.